Continuous glucose monitoring in the ICU: clinical considerations and consensus - James S. Krinsley; J. Geoffrey Chase; Jan Gunst; Johan Martensson; Marcus J. Schultz; Fabio S. Taccone; Jan Wernerman; Julien Bohe; Christophe De Block; Thomas Desaive; Pierre Kalfon; Jean-Charles Preiser (Critical Care, 2017)
Abstract Glucose management in intensive care unit (ICU) patients has been a matter of debate for almost two decades. Compared to intermittent monitoring systems, continuous glucose monitoring (CGM) can offer benefit in the prevention of severe hyperglycemia and hypoglycemia by enabling insulin infusions to be adjusted more rapidly and potentially more accurately because trends in glucose concentrations can be more readily identified. Increasingly, it is apparent that a single glucose target/range may not be optimal for all patients at all times and, as with many other aspects of critical care patient management, a personalized approach to glucose control may be more appropriate. Here we consider some of the evidence supporting different glucose targets in various groups of patients, focusing on those with and without diabetes and neurological ICU patients. We also discuss some of the reasons why, despite evidence of benefit, CGM devices are still not widely employed in the ICU and propose areas of research needed to help move CGM from the research arena to routine clinical use.